Author Correction: The discovery of Bombali virus adds further support for bats as hosts of ebolaviruses. (December 2018) - Goldstein, Tracey; Anthony, Simon; Gbakima, Aiah; Bird, Brian; Bangura, James; Tremeau-Bravard, Alexandre; Belaganahalli, Manjunatha; Wells, Heather; Dhanota, Jasjeet; Liang, Eliza; Grodus, Michael; Jangra, Rohit; et al.
In the version of this Article originally published, the bat species for 12 individuals were incorrectly identified in Supplementary Table 1 and 2. After resequencing theMT-CytB andMT-CO1 segments and reviewing the data, the authors have corrected the errors for these 12 animals. In the amended version of the Supplementary Information, Supplementary Tables 1 and 2 have been replaced to include the corrected host species information. None of the 12 bats affected were positive for the Bombali virus, and the conclusions of the study are therefore unchanged.